Formulasi Sediaan Serum Antioksidan dari Ekstrak Sari Tomat (Solanum Lycopersicum L.) sebagai Perawatan Kulit - Hanita Christiandari; Intan Kumalawati; Jarot Yogi Hernawan (STIKes Ibnu Sina Ajibarang, 2025)
Skin damage occurs because free radicals lose one electron in their outer orbit so that they are highly reactive which can cause oxidative stress. The impact is damage to body cells, such as large pores, acne, wrinkles and dark spots. Free radicals can come from the metebolism process in the body and from outside the body. One preparation that can prevent skin damage is a serum that contains antioxidants. To determine the physical properties, namely organoleptics, homogeneity, pH, spreadability, and adhesiveness of tomato juice extract (Solanum lycopersicum L.) serum preparations. The type of research used is experimental. The sample used was tomato juice extract. The research was conducted at the Pharmacy Laboratory of Politeknik Permata Indonesia Yogyakarta in May-June 2024. The independent variables of this study were 2%, 4%, 6% tomato juice extract. The dependent variable in this study is the test of physical properties of serum preparations including organoleptical tests, homogeneity, pH, spreadability, and adhesiveness. Data analysis in this method uses One way ANOVA. Organoleptical results are viscous, clear, clear yellow, light brown to dark brown in color and smells rose. The homogeneity results of the three formulations are homogeneous. The pH value in F0 was 5.08; F1 was 5.20; F2 was 5.35; F3 was 5.51. The value of spreadability in F0 was 5.2cm; F1 was 5.78cm; F2 was 5.91cm; F3 was 6.23cm. The stickiness value in F0 was 8.82; F1 was 15.94; F2 was 23.11; F3 was 30.75. All formulas have organoleptical arrangement, homogeneity, pH, spreadability, and adhesiveness that meet the requirements. Serum preparation of tomato juice extract (Solanum lycopersicum L.) has eligible physical properties.